Cardiovascular System Changes and Related Risk Factors in Acromegaly Patients: A Case-Control Study - Xiaopeng Guo; Lu Gao; Shuo Zhang; Yilin Li; Yue Wu; Ligang Fang; Kan Deng; Yong Yao; Wei Lian; Renzhi Wang; Bing Xing (International Journal of Endocrinology)
Background. Cardiovascular complications are known to be the main determinants of reduced life expectancy and decreased quality of life in acromegaly patients. Our study aimed to provide insight into the cardiovascular changes that occur in acromegaly patients and to investigate the correlative risk factors. Methods. A total of 108 patients definitively diagnosed with acromegaly and 108 controls matched for age and gender were recruited into study and control groups, respectively. Standard echocardiography was performed on all of the participants, and data were collected and analyzed. Results. All acromegaly patients presented with structural cardiac changes, including a larger heart cavity, thicker myocardial walls, and increased great vessel diameters compared with the control group. Additionally, the acromegaly patients presented with reduced diastolic function. Aging and increased body mass index (BMI) were correlated with myocardial hypertrophy and diastolic dysfunction; a longer disease duration was correlated with larger great vessel diameters. Conclusions. Ageing and increased BMI are independent risk factors for acromegalic cardiomyopathy, and a long disease duration results in the expansion of great vessels. Increased efforts should be made to diagnose acromegaly at an early stage and to advise acromegaly patients to maintain a healthy weight.